Efficacy of Cow Urine as Plant Growth Enhancer and Antifungal Agent - Savita Jandaik; Preeti Thakur; Vikas Kumar (Advances in Agriculture)
The present study was conducted to determine antifungal activity of three different concentrations (5, 10, and 15%) of cow urine against three fungal pathogens (Fusarium oxysporum, Rhizoctonia solani, and Sclerotium rolfsii) isolated from infected plants of Methi and Bhindi that showed symptoms of damping off and wilting disease by poison food technique. The extent of growth of test fungi in plates poisoned with cow urine was lesser when compared with the control plates. Among these concentrations cow urine at 15% concentration was most effective. When the three fungal organisms were compared, maximum growth suppression was observed in Fusarium oxysporum (78.57%) at 15% concentration of cow urine followed by Rhizoctonia solani (78.37%) and Sclerotium rolfsii (73.84%). Finally we concluded that the cow urine has antifungal activities and the inhibitory activity can be used in the control of fungi. The nutritional effect of cow urine on plant growth was also tested with Trigonella foenum-graecum (Methi) and Abelmoschus esculentus (Bhindi) plants and the chlorophyll and protein content was also estimated.